PELUANG PENGEMBANGAN WISATA LINTAS BATAS (CROSS-BORDER TOURISM) DALAM MENINGKATKAN PERTUMBUHAN EKONOMI KABUPATEN SAMBAS - Desi Yuniarti (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The number of tourist visits to Sambas Regency is low but every year it increases to Temajuk Village Tourism. This study aims to analyze the characteristics of tourism actors, tourism potential, tourism development practices, and tourism development factors in Temajuk Village. This case study research collects data from interviews, observations, and focus group discussions (FGD). Informants in the study were selected using a purposive sampling technique based on the characteristics of tourism actors. Testing data through source triangulation, interactive model data analysis using social practice theory from Bourdieu. The results showed that the characteristics of tourism actors consisted of domestic and foreign tourists. tourism service industries such as villas, resorts and homestays, travel agencies